Management of “O” Positive Patient, Transfused with “B” Positive Blood – A Case Report - Nahar, Kamrun; Raihan, Sk Golam; Binni, Sabrina Yeasmin; Ahsan, Ishrat Nandini; Ibne Momen, Abdul Basit (Chest & Heart Journal, 2021)
The complications of blood transfusion are well known and at times is life threatening especially when it occurs due to accidental major mismatched blood transfusion. Here we present a case of a 32 years old lady who delivered a baby by LUCS. On her 3rd POD, she came to a tertiary level hospital with profuse per vaginal bleeding, breathlessness. She received an erroneous transfusion of group “B” Rh positive blood when her actual blood group was “O” Rh positive at a different hospital. She presented with features of DIC and acute renal failure. She was admitted to critical care unit- treated with broad spectrum antibiotics, forced diuresis with inj. Frusemide and eventually 3 sessions of hemodialysis were needed. As for transfusion, we decided to transfuse her with “O” Rh positive washed packed cell and “AB” Rh positive plasma which finally saved her life. Chest Heart J. 2020; 44(2) : 112-115